Favela tour experience: the impacts in the host communities - Silva, Natalia Gonçalves da (2021)
Tourism sector has constantly evolved to the different necessities of the population – from ordinary tourism experiences to tailor made ones. It is in this scenario that tourism performed in slums has been created, raising the interest of researchers and generating controversial opinions regarding its objectives. For this reason, the present study aims to verify the impacts of the slum tours in the host communities by analyzing the pre-concepts and ideas associated with this tourism activity through the collection of data attained by the application of a survey, comparing it with the results obtained during the visits to the slums of Rocinha and Santa Marta – both located in the city of Rio de Janeiro, Brazil. For its validity, the research performed by Freire-Medeiros, Frenzel, Koven, Menezes, Nisbett, Dyson, Dürr, and others are used as a guidance reference allowing the reader to have a broader perspective of the phenomena here presented. As for the obtained results, the study shows that the benefits of the tours for the communities mentioned previously can be divided in two types: tangible and intangible - the first refers to the economic advantages of the tour; whereas the second one refers to the change in perspective and reduction of the prejudice suffered by the inhabitants of those areas.